CHALLENGES AND OPPORTUNITIES OF DAIRY SECTOR IN INDIA VIS-À-VIS WORLD: A CRITICAL REVIEW - Avijit Sarkar; Avijan Dutta (Exploratory Animal and Medical Research, 2020)
Globally, dairy sector is undergoing phenomenal changes in terms of technology, feed quality, health & quality of breed, quality assurance, equipment & machineries, diversification of milk products and marketing concept. This is forcing the dairy sector to relook at the current strategy. With consideration of existing challenges and opportunities at milk producers, milk processors, marketers and consumers level, this review article has outlined overarching viewpoints and subsequently, has explored how the dairy sector needs to adapt. Study has been extended from global to National level including the state of West Bengal. Indian Dairy sector needs to take care of a few basic problems like shortage of quality feed & fodder, quality bovine breed and below par milk producers’ selling price. In addition, a few relevant opportunities should be availed through co-product generation as a part of holistic approach in handling dairy farming and dairy industry. In view of significant socio-economic dependency in Indian context, revenue model needs routine exploitation from biogas generation, culling of unproductive animals, adoption of economies of scale at milk federation level and effective institutionalization in states like West Bengal to establish this dairy sector as a sustainable source of livelihood.